POLIGAMI DALAM PEMIKIRAN KH HUSEIN MUHAMMAD PERSPEKTIF SOSIOLOGI HUKUM (Ahkam: Jurnal Hukum Islam, 2024)
Polygamy has been interestingly discussed and giving rise to pros and cons with its all related arguments until now. This paper aims to analyze polygamy based on the thinking of KH Husein Muhammad and is strengthened by the theory of legal sociology. This research is qualitative, particularly the type of library research, and uses a conceptual approach. According to KH Husein Muhammad's thought, polygamy is not a practice born out of Islamic tradition. Islam did not initiate polygamy. Long before Islam came, the polygamy tradition had become a form of patriarchal civilization practice. According to KH Husein Muhammad, there must be an effort to reconstruct the Marriage Law related to polygamy. The phenomenon that is often encountered is a bad situation due to polygamy which can gradually harm the future of the nation's generation. This situation is immediately resolved by all parties, both the public and the state, through the improvement of laws or regulations. Referring to the process of gradual improvement as exemplified by the al-Qur'an for many cases, including cases of slavery, it is time for the process towards monogamous marriage to be carried out. Although the Qur'an mentions the issue of polygamy in Surah an-Nisa'(4): 3, however, there is a Hadis of the Prophet Muhammad that opposed Ali bin Abi Talib's plan to polygamy on Fatimah ra. KH Husein Muhammad criticized several manhajs of polygamy by arguing that monogamy rejects more harm than polygamy does. Therefore, monogamy must take precedence to be implemented because polygamy which causes arbitrary actions and endangers his wife and children must be avoided, in accordance with a sociological view of law, namely looking at law or norms from a social aspect.
Keywords: Polygamy; Legal Sociology; KH Husein Muhammad